FYCO1 regulates cardiomyocyte autophagy and prevents heart failure due to pressure overload in vivo - Kuhn, Christian; Menke, Maja; Senger, Frauke; Mack, Claudia; Dierck, Franziska; Hille, Susanne; Schmidt, Inga; Brunke, Gabriele; Bünger, Pia; Schmiedel, Nesrin; Will, Rainer D.; Sossalla, Samuel; et al. (JACC Basic to translational science, 2021)
Autophagy is a cellular degradation process that has been implicated in diverse disease processes. The authors provide evidence that FYCO1, a component of the autophagic machinery, is essential for adaptation to cardiac stress. Although the absence of FYCO1 does not affect basal autophagy in isolated cardiomyocytes, it abolishes induction of autophagy after glucose deprivation. Likewise, Fyco1-deficient mice subjected to starvation or pressure overload are unable to respond with induction of autophagy and develop impaired cardiac function. FYCO1 overexpression leads to induction of autophagy in isolated cardiomyocytes and transgenic mouse hearts, thereby rescuing cardiac dysfunction in response to biomechanical stress.
Gesehen am 28.07.2021